PERFORMANCE EVALUATION OF CO–OPERATIVE SOCIETIES IN KARIMNAGAR DISTRICT - A COMPARATIVE STUDY - M.H.V. BHAVE, B. VIJAY KUMAR, T. LAVANYA, R. VIJAYA KUMARI and (The Journal of Research, PJTSAU, 2019)
Credit is occupying an important place in the strategy for development of agriculture. Credit is a critical input that affects agricultural and rural productivity along with the other inputs. Credit is important enough to establish causality with productivity. Indian farmers are unable to meet their increased capital needs out of funds generated on the farm (Calkins and Ngo, 2005). Due to inadequate financial resources and absence of timely credit facilities at reasonable rates, many of the farmers, even though willing, are unable to go in for improved package of practices or to introduce better methods in agriculture The agricultural credit system of India consists of informal and formal sources of credit supply. The informal sources like commission agents, traders, private money lenders etc. are major channels for distribution. Formal credit in India includes commercial banks, cooperatives and micro-finance institutions (Carla and Dohmwirth, 2014).